DEVELOP THE FINANCING OF PUBLIC-PRIVATE PARTNERSHIP (PPP) PROJECTS - Marzok, Mohamed Mahdy; Elhessnawi, Mahmoud Omar (Acta Scientiae et Intellectus, 2024)
Public private partnerships (PPPs) are procurement models used in the provision of public infrastructures and involving private, as opposed to public, finance. The PPP model differs from the traditional public procurement model in this sense and in the unprecedented degree to which the private sector is involved. All things being equal, the rationale for choosing a PPP instead of a traditional public procurement model is if it provides a better Value for Money. As a result, a crucial issue to address is to find the key drivers of Value for Money in PPP projects and most importantly, to analyze the relationships between those key drivers and the complex notion of Value for Money.This study is based on a large overview of the literature together with contributions of informal interviews and my own opinions. Emphasis is put on the importance of risk management from financiers’ perspective and its consequences on Value for Money. The findings highlight the current problems in the Value for Money assessment that make the analysis hardly reliable. Good and bad practices in Value for Money assessment are discussed and potential solutions and guidance toward more Value for Money are provided.